THE IMPACT OF MOBILE GADGET IN EFL LEARNING: PERCEPTIONS OF EFL UNDERGRADUATES - Imam - Fauzi (Universitas Muhammadiyah Tangerang, 2018)
AbstractMost of young people are enthusiasticin having the most recent mobile gadgets just to boast among their peers. They likely utilize them to make phone calls, take pictures, listen to songs, watch videos, or surf the internet access for learning or just entertainment. In a technologically advanced country like Indonesia, the third and fourth generation (3G, 4G) mobile devices are available at affordable prices, and people of all streams find it necessary to own a mobile gadget for connecting and communicating. Moreover, it has become a common trend among undergraduates to carry a mobile gadget to the classroom as well.In this paper, the researcher emphasize the potential of mobile gadgets as a learning tool for students and have incorporated them into the learning environment.The present study examines the application of mobile gadgetin EFL learning and investigates the perceptions of EFL students about mobile gadget in learning activity. A field study was conducted on thirty undergraduatestudents majoring in accounting study Serang Raya University. The methodology of data collection included a self-report for students and teachers’ and students’ questionnaire. Findings of the research are significant for EFL teachers and researchers for introducing innovative methods and helpful materials for the English classroom.Keywords: Mobile gadget, students’ perception, teachers’ perception..